Role and molecular mechanism of traditional Chinese medicine in preventing cardiotoxicity associated with chemoradiotherapy - Lv, Xin-Fang; Wen, Ruo-Qing; Liu, Kai; Zhao, Xin-Ke; Pan, Chen-Liang; Gao, Xiang; Wu, Xue; Zhi, Xiao-Dong; Ren, Chun-Zhen; Chen, Qi-Lin; Lu, Wei-Jie; Bai, Ting-Yan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Cardiotoxicity is a serious complication of cancer therapy. It is the second leading cause of morbidity and mortality in cancer survivors and is associated with a variety of factors, including oxidative stress, inflammation, apoptosis, autophagy, endoplasmic reticulum stress, and abnormal myocardial energy metabolism. A number of studies have shown that traditional Chinese medicine (TCM) can mitigate chemoradiotherapy-associated cardiotoxicity via these pathways. Therefore, this study reviews the effects and molecular mechanisms of TCM on chemoradiotherapy-related cardiotoxicity. In this study, we searched PubMed for basic studies on the anti-cardiotoxicity of TCM in the past 5 years and summarized their results. Angelica Sinensis, Astragalus membranaceus Bunge, Danshinone IIA sulfonate sodium (STS), Astragaloside (AS), Resveratrol, Ginsenoside, Quercetin, Danggui Buxue Decoction (DBD), Shengxian decoction (SXT), Compound Danshen Dripping Pill (CDDP), Qishen Huanwu Capsule (QSHWC), Angelica Sinensis and Astragalus membranaceus Bunge Ultrafiltration Extract (AS-AM),Shenmai injection (SMI), Xinmailong (XML), and nearly 60 other herbs, herbal monomers, herbal soups and herbal compound preparations were found to be effective as complementary or alternative treatments. These preparations reduced chemoradiotherapy-induced cardiotoxicity through various pathways such as anti-oxidative stress, anti-inflammation, alleviating endoplasmic reticulum stress, regulation of apoptosis and autophagy, and improvement of myocardial energy metabolism. However, few clinical trials have been conducted on these therapies, and these trials can provide stronger evidence-based support for TCM.